Resection of supratentorial brain metastases with intraoperative radiotherapy. Is it safe? Analysis and experiences of a single center cohort - Krauss, Philipp; Steininger, Kathrin; Motov, Stefan; Sommer, Bjoern; Bonk, Maximilian Niklas; Cortes, Abraham; Wolfert, Christina; Stueben, Georg; Shiban, Ehab; Kahl, Klaus Henning (Frontiers in Surgery, 2022)
Introduction: Intraoperative Radiotherapy (ioRT) is an emerging treatment option in oncologic surgery for various diseases including intraaxial brain lesions to improve surgical outcome and accelerate the adjuvant oncologic therapy. Despite its use in glioma surgery, the application and data regarding ioRT in the treatment of brain metastases (BMs) is sparse. Here were report the largest series of supratentorial BMs treated with resection and ioRT according to functional outcome and adverse events. Methods: We performed a retrospective chart review analysis of patients undergoing surgery for BMs following an interdisciplinary tumor board decision in every case with ioRT at our institution. Patient properties, functional status (Karnofsky Performance Score/KPS) before and after surgery as well as oncologic (disease, recursive partitioning analysis, lesion size) and operative parameters were analyzed until hospital discharge. Adverse events (AE) were recorded until 30 days after surgery and rated according to the Clavien Dindo Rating scale. Results: 70 patients (40 female) with various oncologic diseases were identified and analyzed. Six underwent prior RT. Mean age was 66±11 years. Preoperative median KPS was 80% with a mean BM volume of 3.2±1.2cm3. Nine patients experienced in total 14 AEs, including 2 cases of postoperative death. After surgery, the neurological status in 7 patients deteriorated while it improved in 21 cases. Patients experiencing AEs had longer hospitalization and poorer postoperative KPS mdn. 90 vs. 80%. Deterioration was not associated to any surgical parameter. However, overall, there was no statistically significant deterioration of the functional status during the immediate postoperative course. Conclusion: Surgery for supratentorial BMs with ioRT seems safe and feasible. Further studies on the benefit regarding oncologic outcome need to be performed.